Artistic interventions as a reflection of introspection in adolescence - Acosta García, Laula; Lopez-Ruiz, David (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2024)
This study presents the design and implementation of an intervention proposal based on the self-portrait as an exercise of introspection in first year students of Artistic Baccalaureate. Through a theoretical-practical analysis, the importance of the construction of identity during adolescence and the transition that the human being experiences during adolescence, as well as the benefits of Art Education as a means of establishing a connection between students and their emotions, are explored in depth. The artistic project developed has allowed to combine the most emotional part of the individual with the practice through modeling and sculpture in order to establish a positive personal and social development. Through this intervention, participants have been able to validate and understand their emotional repertoire, valuing the importance of creating a space in the classroom where they feel safe through various introspective exercises around art. The results obtained show a greater motivation and creativity of the students, as well as a constructive transfer of their own emotions developed during the artistic process.